1994
DOI: 10.2105/ajph.84.4.587
|View full text |Cite
|
Sign up to set email alerts
|

Low-income neighborhoods and the risk of severe pediatric injury: a small-area analysis in northern Manhattan.

Abstract: OBJECTIVES. The purpose of this study was to investigate the relationship between socioeconomic disadvantage and the incidence of severe childhood injury. METHODS. Small-area analysis was used to examine socioeconomic risk factors for pediatric injury resulting in hospitalization or death in Northern Manhattan, New York, NY, during a 9-year period (1983 through 1991). RESULTS. The average annual incidence of all causes of severe pediatric injury was 72.5 per 10,000 children; the case-fatality rate was 2.6%. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
0
11

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(122 citation statements)
references
References 26 publications
5
106
0
11
Order By: Relevance
“…Two studies examined correlations between all nonfatal injury rates among youth and SES, one in Australia (33) and the other in New Zealand (65); both found that injury rates were inversely correlated with measures of area SES. Two studies used the same data source (Northern Manhattan Injury Surveillance System) to examine severe injuries (those resulting in hospitalization or death) but utilized two different levels of analysis: zip code of residence (23) and census tract (22). Both studies found that low SES was associated with higher injury rates among persons ages 16 and under. For the studies examining cause-specific nonfatal injuries, rates were higher in areas characterized by low SES, or inversely correlated with SES measures for head injuries (24,41,60), fire or burn injuries (32,47), pedestrian or bicyclist injuries (21,63), and intentional nonfatal injuries (28), regardless of study population and setting, source of data, covariates, or SES measure(s) used.…”
Section: Nonfatal Injuriesmentioning
confidence: 99%
“…Two studies examined correlations between all nonfatal injury rates among youth and SES, one in Australia (33) and the other in New Zealand (65); both found that injury rates were inversely correlated with measures of area SES. Two studies used the same data source (Northern Manhattan Injury Surveillance System) to examine severe injuries (those resulting in hospitalization or death) but utilized two different levels of analysis: zip code of residence (23) and census tract (22). Both studies found that low SES was associated with higher injury rates among persons ages 16 and under. For the studies examining cause-specific nonfatal injuries, rates were higher in areas characterized by low SES, or inversely correlated with SES measures for head injuries (24,41,60), fire or burn injuries (32,47), pedestrian or bicyclist injuries (21,63), and intentional nonfatal injuries (28), regardless of study population and setting, source of data, covariates, or SES measure(s) used.…”
Section: Nonfatal Injuriesmentioning
confidence: 99%
“…Potential confounders of forearm fracture risk and/or general injury risk include age, 41 gender, 41 parental education level/socioeconomic status, 42 season, 43,44 activity level, 45 high BMI, 12,13 height, 46 dietary calcium intake, 17 BMD, [11][12][13][14][15][16] and 25-hydroxyvitamin D status. [18][19][20][21][22][23] Because 25-hydroxyvitamin D status may be a strong determinant of BMD, [18][19][20][21] we also modeled the association of fracture status with BMD separately without 25-hydroxyvitamin D. For the same reason, we also modeled the association of fracture status with 25-hydroxyvitamin D separately without BMD while controlling for the same potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Çocuk yaralanmaları açısından risk faktörlerinin araştırıldığı bir çalışmada, düşük sosyo-ekonomik dü zey, parçalanmış aile, düşük eğitim düzeyi ve işsizli ğin hem kasıtlı hem kasıtsız çocuk yaralanmaları için önemli risk faktörleri olduğu, şiddet yaralanmalarının düşük sosyoekonomik kesimde 4.5 kat fazla olduğu saptanmış, şiddet önleme çabalarında sosyoekonomik eşitsizliklerin göz önüne alınması gerektiği bildirilmiş tir (8).…”
Section: Introductionunclassified